(untitled) (Research, Society and Development, 2022)
Melipona males are an important link in the reproductive caste in hives and colonies of these stingless bees. In these they perform several functions, but the fundamental one is to contribute, in partnership with princesses, to the continuity of the species in the environments. Melipona eburnea Friese 1900 ("uruçu-beiço") has a geographical distribution in South America (including Brazil), while M. seminigra merrillae Cockerell, 1920 ("uruçu-boca-de-renda") is restricted to states, especially, in the Northern Region of Brazil. Both species are promising for Meliponiculture because of their productivity, ease of rearing and management. This observational study aimed to understand, under laboratory conditions, some biological and ethological aspects of males of these species. The original colonies were adapted to the observation box. Then hatched brood disks were obtained from these and placed in ideal temperature and humidity conditions. Immediately after hatching, males were marked on the thorax with coloured and numbered labels using non-toxic glue. They were then placed in the colonies and accepted by the other bees. Observations were made during the rainy season of 2003 (M. s. merrillae) and 2005 (M. eburnea), in the morning, between 07:00-09:00 h and between 10:00-12:00 h. The length of stay or longevity and survival of males in the colony was lower in M. eburnea and higher in M. s. merrillae. Survival curves were convex. Males of both species, after leaving the colonies, did not return. The ethe (behaviours) detected were classified into seven categories: body cleaning, immobility, mobility, incubation, cerumen work, trophallaxis and queen reverence.